Moderate Islamic Boarding School Education - Ilmiah, Rikhlatul; Zaghloul, Taha Romadhan; Pristine, Depict (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2023)
The challenges faced by Pesantren today are not only the ability to consume all classical tradition materials but the development of modern culture and civilization has implications for socio-culture in society. The bigger challenge faced by Pesantren is openness to moderate thoughts, thinking scientifically and with a comprehensive perspective. Diniyah higher education or Ma'had Aliy provides a new pattern as Pesantren education which maintains the continuity of the tradition of classical texts while providing